Minimal invasive approach for Giant Pulmonary Hydatid cyst (Journal of Society of Surgeons of Nepal, 2021)
Hydatid cyst is a major health problem in agricultural countries caused by larval stage of Echinococcus granulosus. Hydatid cysts of 10 cm or greater in diameter are called “giant” cysts and traditionally have been considered to be more difficult to treat surgically.A 30 year male presented with complaints of cough and chest pain for three days and a CECT chest suggesting lung abscess. When thoroughly evaluated with bedside ultrasound, it was revealed to be a case of giant Hydatid cyst. The patient underwent cystostomy with closure of bronchial opening with capitonnage with minimal invasive approach (VATS assisted minithoracotomy).Even Giant Hydatid cyst can be managed with VATS, avoiding formal thoracotomy. Preoperative sonoscopy can localize the exact site for port placement and guide the surgeons on the operation table.